Paired-Pulse Inhibition in the Auditory Cortex in Parkinson's Disease and Its Dependence on Clinical Characteristics of the Patients. (3rd October 2010) - Lukhanina, Elena; Berezetskaya, Natalia; Karaban, Irina
Abstract : We aimed to determine the value of the paired-pulse inhibition (PPI) in the auditory cortex in patients with Parkinson's disease (PD) and analyze its dependence on clinical characteristics of the patients. The central (Cz) auditory evoked potentials were recorded in 58 patients with PD and 22 age-matched healthy subjects. PPI of the N1/P2 component was significantly( P < .001 ) reduced for interstimulus intervals 500, 700, and 900 ms in patients with PD compared to control subjects. The value of PPI correlated negatively with the age of the PD patients( P < .05 ), age of disease onset( P < .05 ), body bradykinesia score( P < .01 ), and positively with the Mini Mental State Examination (MMSE) cognitive score( P < .01 ) . Negative correlation between value of PPI and the age of the healthy subjects( P < .05 ) was also observed. Thus, results show that cortical inhibitory processes are deficient in PD patients and that the brain's ability to carry out the postexcitatory inhibition is age-dependent.